The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/2014jd022173
|View full text |Cite
|
Sign up to set email alerts
|

Improving the representation of clouds, radiation, and precipitation using spectral nudging in the Weather Research and Forecasting model

Abstract: Spectral nudging-a scale-selective interior constraint technique-is commonly used in regional climate models to maintain consistency with large-scale forcing while permitting mesoscale features to develop in the downscaled simulations. Several studies have demonstrated that spectral nudging improves the representation of regional climate in reanalysis-forced simulations compared with not using nudging in the interior of the domain. However, in the Weather Research and Forecasting (WRF) model, spectral nudging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 43 publications
1
34
1
Order By: Relevance
“…Spectral nudging has proven to be dampening physical parameterizations variability less than analysis nudging [59]. Also, studies for regional climate modelling have shown that analysis nudging is less efficient for sensitivity analyses in high resolution as it results in extinguishing fine-scale variability [60]. Additionally, spectral nudging can fade out extreme events as it drives the model toward a smoother, larger-scale state [61].…”
Section: Spectral Nudgingmentioning
confidence: 99%
“…Spectral nudging has proven to be dampening physical parameterizations variability less than analysis nudging [59]. Also, studies for regional climate modelling have shown that analysis nudging is less efficient for sensitivity analyses in high resolution as it results in extinguishing fine-scale variability [60]. Additionally, spectral nudging can fade out extreme events as it drives the model toward a smoother, larger-scale state [61].…”
Section: Spectral Nudgingmentioning
confidence: 99%
“…Successfully constraining the mesoscale simulation to follow the synoptic-scale driving fields by spectral nudging was key to reproducing the precipitation in the southern Great Plains in our case. This benefit, while maintaining the ability of the mesoscale models to develop small-scale dynamics, allowed successful applications of spectral nudging in dynamical downscaling of precipitation (GarcĂ­a-Valdecasas Ojeda et al, 2017;Huang et al, 2016;Liu et al, 2012;Lo et al, 2008;Mabuchi et al, 2002;Miguez-Macho et al, 2004;Paul et al, 2016;Spero et al, 2014;von Storch et al, 2000). To achieve the best simulation of August precipitation climatology in this study, we used the spectral nudging configurations (including nudging strength, nudging height, and wave numbers) as suggested by Wang and Kotamarthi (2014) on the WRF downscaling simulations for the August of all 14 years.…”
Section: High-resolution Dynamic Downscaling Of August Climatementioning
confidence: 99%
“…However, in general, there exist large uncertainties with dynamic downscaling. RCMs have been found to be sensitive to spatial resolution (Lee et al, ; Tripathi & Dominguez, ; Yamada et al, ), nudging strategies (Bowden et al, ; Bullock et al, ; Harkey & Holloway, ; Liu et al, ; Miguez‐Macho et al, ; Omrani et al, ; Otte et al, ; Spero et al, ; Wang & Kotamarthi, ), model reinitialization frequency (Lo et al, ; Pan et al, ; Qian et al, ), and physics parameterizations such as cumulus schemes (Choi et al, ; Gochis et al, ; Liang et al, ; Pohl et al, ; Qiao & Liang, ) and land surface models (Bukovsky & Karoly, ; Chen et al, ; Vidale et al, ). Given these uncertainties, confidence in RCM‐downscaled projections of future climate can only be achieved when the credibility of RCM downscaling of historical climate has been proven (Gutowski et al, ; Harding & Snyder, ; Kendon et al, ; Liang et al, ; Mearns et al, ; Wehner, ; Xue et al, ).…”
Section: Introductionmentioning
confidence: 99%